All-digital thermal distribution measurement on field programmable gate array using ring oscillators. Issue 2 (February 2015) - Yue, Yuan; Feng, Shi-Wei; Guo, Chun-Sheng; Yan, Xin; Feng, Rui-Rui
Highlights: The transient thermal of field programmable gate array based systems could be measured. An array of sensors can be placed in any position of the die construct a thermal map. We use the infrared techniques to capture the thermal imagers to compare with sensors. The signals of sensor are digital, there is no analog digital to interfere. Abstract: In this paper, a digital method for transient temperature distribution measurement of field programmable gate array (FPGA)-based systems is proposed. The smart thermal sensors used rely on correspondence between the delay and temperature in a ring oscillator. The tested temperature was converted into a time signal with a thermally-sensitive width. The output frequency is read out by a counter with a scan path, and then, transited to PC by a Universal Serial Bus (USB) interface. We capture the infrared images of the FPGA chip by infrared camera. The images were compared with the thermal map of the die constructed using an array of sensors. The tested temperature error varies by less than 1.6 °C in the range from 20 °C to 90 °C, and the maximum sampling rate is 330 Hz.